Produção, nutrição e fitossanidade de cultivares de tomateiro, sobmanejo orgânico - Debora da Silveira Toledo (2008)
The indiscriminate use of agrochemical products on tomato crops, besides increasing production costs, has damaged the producers and consumers health and also the environment. The organic management, together with the use of adapted varieties may be a viable alternative to minimize these negative impacts. Thus, this work had as an aim to evaluate the production, nutrition and phytosanity of tomato tree cultivars under the organic management during summer in the city of Montes Claros, State of Minas Gerais, Brazil. The treatments consisted of four open pollination tomato cultivars (Chadwick Cherry, Red Pitanga, Santa Clara and Santa Cruz Kada) and five hybrid cultivars (Marguerita, Nicolas, Ellen, Magestade and Dominador). The experimental design of randomized blocks with three replicates was used. The following characteristics were evaluated: the number of racemes per plant, the total and commercial numbers of fruit per plant, the percentage of commercial fruit, the average fruit weight, the production, the commercial production, percentage of fruit per largeness class, the nutritional balance of the plants, the incidence of tomato spotted wilt virus in the plants of these cultivars along their phenological ages (35, 49, 63, 77 and 91 days aftertillage), the frequence of insect in the plants along their phenological ages (29, 36, 43, 50, 57, 64, 71, 78 and 85 days after tillage) and the fruit loss percentage by the attack of wood borers, rot, cracking and non commercial size. The cultivar Chadwick Cherry stood out for its higher commercial fruit production, bigger uniformity, less frequency of sucker insects in the plants, thus being the most tolerant cultivar in the tillage conditions of the experiment. All the cultivars presented low potassium and manganese content in the leaf which contributed together with phytosanitary factors to decrease the production.